Incoherent Feedforward Regulation via Sox9 and ERK Underpins Mouse Tracheal Cartilage Development - Yoshida, Takuya; Matsuda, Michiyuki; Hirashima, Tsuyoshi (Frontiers in Cell and Developmental Biology, 2020)
Tracheal cartilage provides architectural integrity to the respiratory airway, and defects in this structure during embryonic development cause severe congenital anomalies. Previous genetic studies have revealed genes that are critical for the development of tracheal cartilage. However, it is still unclear how crosstalk between these proteins regulates tracheal cartilage formation. Here we show a core regulatory network underlying murine tracheal chondrogenesis from embryonic day (E) 12.5 to E15.5, by combining volumetric imaging of fluorescence reporters, inhibitor assays, and mathematical modeling. We focused on SRY-box transcription factor 9 (Sox9) and extracellular signal-regulated kinase (ERK) in the tracheal mesenchyme, and observed a synchronous, inverted U-shaped temporal change in both Sox9 expression and ERK activity with a peak at E14.5, whereas the expression level of downstream cartilage matrix genes, such as collagen II alpha 1 (Col2a1) and aggrecan (Agc1), monotonically increased. Inhibitor assays revealed that the ERK signaling pathway functions as an inhibitory regulator of tracheal cartilage differentiation during this period. These results suggest that expression of the cartilage matrix genes is controlled by an incoherent feedforward loop via Sox9 and ERK, which is supported by a mathematical model. Furthermore, the modeling analysis suggests that a Sox9-ERK incoherent feedforward regulation augments the robustness against the variation of upstream factors. The present study provides a better understanding of the regulatory network underlying the tracheal development and will be helpful for efficient induction of tracheal organoids.